A = 3x2 + 9xy + 6y2l = 3x + 6yA = l×w∴ w = A/l∴ w = (3x2 + 9xy + 6y2) / (3x + 6y)∴ w = x + 1
(x - 2)(9y - 2)
3/35z
It is not clear whether the spaces that appear between some xy pairs are intentional or whether they should have had some other symbols. Ignoring those spaces, 21xy + 28.
9xy(3xy - 4)
The given equation: =3x-4x plus 9xy-12y =3x-4x+9xy-12y =-x+9xy-12y =-x+3y(3y-4) Answer.
A = 3x2 + 9xy + 6y2l = 3x + 6yA = l×w∴ w = A/l∴ w = (3x2 + 9xy + 6y2) / (3x + 6y)∴ w = x + 1
9xy
(x - 2)(9y - 2)
-9
The GCF is 9xy
If by "What is the answer to", you mean "How do you factor", then we can solve it as follows: x2 + 13xy + 36y2 = x2 + 4xy + 9xy + 36y2 = x(x + 4y) + 9y(x + 4y) = (x + 9y)(x + 4y)
The GCF of 9 and 6 is 3.
3/35z
It is not clear whether the spaces that appear between some xy pairs are intentional or whether they should have had some other symbols. Ignoring those spaces, 21xy + 28.
It is: 3y(2y-3x) when factored
9xy(3xy - 4)